2013
DOI: 10.1016/j.energy.2013.06.011
|View full text |Cite
|
Sign up to set email alerts
|

The effects of FEC (fluoroethylene carbonate) electrolyte additive on the lithium storage properties of NiO (nickel oxide) nanocuboids

Abstract: Guo, Z. (2013). The effects of FEC (fluoroethylene carbonate) electrolyte additive on the lithium storage properties of NiO (nickel oxide) nanocuboids. Energy, 58 (September), 707-713.The effects of FEC (fluoroethylene carbonate) electrolyte additive on the lithium storage properties of NiO (nickel oxide) nanocuboids AbstractNanocuboid shaped NiO (nickel oxide) has been synthesized using an optical floating zone furnace. It was found that the nanocuboids exhibit single crystalline nature, and have clean and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…As shown in Figure S2 (Supporting Information), glucose incorporation is effective in improving the electrochemical performance of CMS, although the rate performance is still quite limited with capacity of <20 mAh g −1 at 5000 mA g −1 . In addition, the initial coulombic efficiency of CMS1 is very limited (<40%), which is possibly related with electrolyte decomposition at low voltage with the formation of solid electrolyte interphase . In this case, in order to boost the electrochemical performance of the samples and to improve the initial CE, ether‐based electrolyte (1 m NaCF 3 SO 3 in diethylene glycol dimethyl ether (DEGDME)) is employed instead, with a narrowed voltage window of 0.5–3.0 V. The cycling stability of metal sulfide‐based materials in ether‐based electrolyte can be enhanced, which is ascribed to the smaller apparent activation energy, reduced voltage polarization, and suppressed polysulfides dissolution in ether‐based electrolyte .…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure S2 (Supporting Information), glucose incorporation is effective in improving the electrochemical performance of CMS, although the rate performance is still quite limited with capacity of <20 mAh g −1 at 5000 mA g −1 . In addition, the initial coulombic efficiency of CMS1 is very limited (<40%), which is possibly related with electrolyte decomposition at low voltage with the formation of solid electrolyte interphase . In this case, in order to boost the electrochemical performance of the samples and to improve the initial CE, ether‐based electrolyte (1 m NaCF 3 SO 3 in diethylene glycol dimethyl ether (DEGDME)) is employed instead, with a narrowed voltage window of 0.5–3.0 V. The cycling stability of metal sulfide‐based materials in ether‐based electrolyte can be enhanced, which is ascribed to the smaller apparent activation energy, reduced voltage polarization, and suppressed polysulfides dissolution in ether‐based electrolyte .…”
Section: Resultsmentioning
confidence: 99%
“…The synergistic effects between the components of the composites as well as the correlation between the composite structure and the electrical performance should be investigated in more detail. In general, the initial CEs of ZnO-based composites were low and should be increased, for which electrolyte optimization, surface modification, and coating of ZnO are possible solutions [ 9 , 48 , 49 ]. In the case of ZnO–MO binary composites, the choice of MO partner to prepare ZnO–MOs may increase the initial CE.…”
Section: Discussionmentioning
confidence: 99%
“…The electrolyte decomposition, SEI formation, occurrence of unclear irreversible reactions, and Li + confinement in the electrode explain the low CE. The authors suggested that electrolyte optimization can enhance the initial CE of the MOs [ 48 , 49 ]. After 200 cycles, the specific capacity of the microspheres remained approximately 1008.6 mAh g −1 .…”
Section: Zno Binary Compositesmentioning
confidence: 99%
“…20 Seng et al showed that the capacity of NiO can increase by as much as 680 mAh g −1 with a PGF. 21 Here we show that an electroactive PGF also forms on our PbSe electrode, adding as much as 300 mAh g −1 to its nominal capacity.…”
mentioning
confidence: 97%